Organic spectroscopy - Yadav, L. D. S. (Kluwer Academic Publishers,Anamaya Publishers, 2005)
Organic Spectroscopy presents the derivation of structural information from UV, IR, Raman, 1H NMR, 13C NMR, Mass and ESR spectral data in such a way that stimulates interest of students and researchers alike. The application of spectroscopy for structure determination and analysis has seen phenomenal growth and is now an integral part of Organic Chemistry courses. This book provides:-A logical, comprehensive, lucid and accurate presentation, thus making it easy to understand even through self-study;-Theoretical aspects of spectral techniques necessary for the interpretation of spectra;-Salient features of instrumentation involved in spectroscopic methods;-Useful spectral data in the form of tables, charts and figures;-Examples of spectra to familiarize the reader;-Many varied problems to help build competence ad confidence;-A separate chapter on ‘spectroscopic solutions of structural problems’ to emphasize the utility of spectroscopy. Organic Spectroscopy is an invaluable reference for the interpretation of various spectra. It can be used as a basic text for undergraduate and postgraduate students of spectroscopy as well as a practical resource by research chemists. The book will be of interest to chemists and analysts in academia and industry, especially those engaged in the synthesis and analysis of organic compounds including drugs, drug intermediates, agrochemicals, polymers and dyes.